The complete mitogenome of the Australian land crayfish Engaeus lyelli (Clark 1936) (Crustacea: Decapoda: Parastacidae). (2nd January 2016) - Gan, Han Ming; Tan, Mun Hua; Lee, Yin Peng; Schultz, Mark B.; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the enigmatic freshwater crayfish Engaeus lyelli was sequenced using the MiSeq Personal Sequencer (Illumina, San Diego, CA). The mitogenome has 16, 027 bp consisting of 13 protein-coding genes, 2 ribosomal subunit genes, 23 transfer RNAs, and a non-coding AT-rich region. The base composition of E. lyelli is 29.01% for T, 27.13% for C, 31.43% for A, and 12.44% for G, with an AT bias of 60.44%. The species has the distinctive gene order characteristic of parastacid crayfish with the exception of some minor rearrangements involving the tRNA genes.